Non-visitors profile for Bukit Bakar Recreation Forest in Kelantan - Mohd Daud, Nur Aqilah (2019)
This study was conducted to describe the profiling of non-visitors market at Bukit Bakar Recreation Forest. Through sampling and interviewers, guided by structured questionnaires to identify the constraint factors that caused the visitors to not go and visit Bukit Bakar Recreation Forest was determined. A total of 100 respondents were interviewed face to face at Machang Town. This research is done to discover the background of non-visitors such as demographic and factors that may be the constraint for the visitors to come and visit this recreation forest. Descriptive analysis was done to evaluate information given by the respondents. Frequency analysis was used to compute percentages of selected variables. From the results, there are five main constraints, identified in the study: worry about personal safety, family members, friends or group are more interested in visiting other attractions, not enough time to visit, not enough information available about the park and their programs and do not like to do any outdoor activities. This study also found a significant correlation between age and worry about personal safety (r = 0.015) also distance to the park is too far (r = 0.038); income and distance to the park is too far (r = 0.014). Besides, there have significant correlation between marital status and do not like to do any outdoor activities (r = <0.0001) also between gender and family members, friends or groups are more interested in visiting other attractions (r = 0.027). Some research implications were elaborated in order to help the related authorities in understanding and managing these factors which may hinder visiting Bukit Bakar Recreation Forest.